Pengaruh Beasiswa Terhadap Motivasi Belajar Mahasasiswa Pendidikan Ekonomi Angkatan 2019 Universitas Negeri Gorontalo - Ismail Van Gobel; Meyko Panigoro; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The purpose of this study was to determine the effect of scholarships on learning motivation, Department of Economics Education, Faculty of Economics, State University of Gorontalo Class of 2019. This study uses a quantitative approach, with survey research methods. The data used is primary data obtained from distributing questionnaires to students of the 2019 Economic Education Study Program. The number of samples in this study was 34 respondents. Data analysis technique using simple linear regression. The results of the study show that there is an effect of scholarships on the learning motivation of students of economic education class of 2019. The magnitude of the influence of scholarships on student learning motivation is 59%, while the rest is influenced by variables not examined by 41%.